"You`re Not Born with Talent" - Talented girls` and boys` perceptions of their talents as football players - Sæther, S. A.; Mehus, I. (Sports, 2016)
Generally in sports, there is a strong assumption of a connection between skill level in young age and adulthood. Studies have mainly focused on the coaches` understanding and role in identifying and developing talent. In this article we turn our attention towards the athletes` perspectives, interviewing talented young football players (five boys and five girls) about their perceptions of their own talent and development. The objective of the article is to investigate how boys and girls perceive their talent and to discuss how various perceptions influence coaching practice in talent development. We introduce the following questions: (a) do the players use a static or dynamic perception of their own talent and (b) do the players consider specific or general skills to be most important in their skill development? Results show that the boys have a more static perception of talent compared to the girls. Furthermore, the boys in this study stress the importance of highly specified skills. The girls have a more balanced view on what is important, but tend to stress the importance of basic skills. The study suggests two potential implications. First, the coaches should be aware of the possible vulnerability following players` static perception of talent. Second, an exclusive focus on specified skills might make for less optimal preparation for the changing demands young players meet when moving through the different levels of play on their way to high level football. In future research it would be interesting to investigate how players with a lower skill level, not yet regarded as talent, perceive their talent and skill development.